The influence of cardiac rehabilitation according to the C model on exercise tolerance and hemodynamic indices in patients after cardiac incident - Ł. Bielawa; K. Prusik; Kr. Prusik (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background and Study Aim: Cardiovascular diseases are currently classified as civilization diseases. The number of cases since the 20th century has dramatically increased. Currently, as many as 46% of all deaths in Poland are caused by diseases of the circulatory system. The aim of the study is to assess the impact of cardiac rehabilitation according to the C model on exercise tolerance and hemodynamic indices in patients after a cardiac incident. Material and Methods: The research was carried out in the Department of Cardiac Rehabilitation in Szymbark. The study group consisted of 32 patients who, after physical examination at admission, were qualified for the preliminary assessment of physical fitness on the basis of 6MWT. The test was carried out the day after the admission, according to current standards. Subsequently, the examined persons underwent a 28-day cycle of early cardiac rehabilitation according to the C model. Results: As a result of a 4-week cardiac rehabilitation, a statistically significant improvement in physical performance was obtained, with a distance increase of 68.34 m on average. A statistically significant change in the level of fatigue according to Skala Borga after the completion of the rehabilitation cycle was demonstrated. Patients with normal body weight, overweight and obesity received a similar increase in 6MWT results due to the rehabilitation cycle. Conclusions: The results of this study indicate the urgent need to educate patients in the prevention and prevention of cardiovascular disease and to increase the availability of rehabilitation for all people after a cardiological incident.